Asymmetric Functional Connectivity of the Contra- and Ipsilateral Secondary Somatosensory Cortex during Tactile Object Recognition - Yu, Yinghua; Yang, Jiajia; Ejima, Yoshimichi; Fukuyama, Hidenao; Wu, Jinglong (Frontiers in Human Neuroscience, 2018)
In the somatosensory system, it is well known that the bilateral secondary somatosensory cortex (SII) receives projections from the unilateral primary somatosensory cortex (SI), and the SII cortex, in turn, sends feedback projections to SI. Most neuroimaging studies have clearly shown bilateral SII activation using only unilateral stimulation for both anatomical and functional connectivity across SII subregions. However, no study has unveiled differences in the functional connectivity of the contra- and ipsilateral SII network that relate to frontoparietal areas during tactile object recognition. Therefore, we used event-related functional magnetic resonance imaging (fMRI) and a delayed match-to-sample (DMS) task to investigate the contributions of bilateral SII during tactile object recognition. In the fMRI experiment, fourteen healthy subjects were presented with tactile angle stimuli on their right index finger and asked to encode three sample stimuli during the encoding phase and one test stimulus during the recognition phase. Then, the subjects indicated whether the angle of test stimulus was presented during the encoding phase. The results showed that contralateral (left) SII activity was greater than ipsilateral (right) SII activity during the encoding phase, but there was no difference during the recognition phase. A subsequent psycho-physiological interaction (PPI) analysis revealed distinct connectivity from the contra- and ipsilateral SII to other regions. The left SII functionally connected to the left SI and right primary and premotor cortex, while the right SII functionally connected to the left posterior parietal cortex. Our findings suggest that in situations involving unilateral tactile object recognition, contra- and ipsilateral SII will induce an asymmetrical functional connectivity to other brain areas, which may occur by the hand contralateral effect of SII.